2015
DOI: 10.3945/jn.115.214577
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Selenium Concentrations Are Sufficient and Associated with Protease Inhibitor Use in Treated HIV-Infected Adults

Abstract: Plasma selenium concentrations were within the normal range for the background population and were not associated with subclinical vascular disease in HIV-infected adults on contemporary ART. The association between current PI use and higher selenium may have implications for ART allocation, especially in resource-limited countries. Also, it appears that statin therapy may increase selenium concentrations; however, larger studies are necessary to confirm this finding. This trial was registered at clinicaltrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…An impairment of selenoprotein biosynthesis may be a factor in congestive heart failure, reminiscent of the dilated cardiomyopathies seen with selenium deficiency [23]. In HIV-infected adults with rosuvastatin treatment, over 48 weeks, Se concentrations increased significantly in the rosuvastatin group [24]. The reason for the inconsistency between our study and this study may be due to the different duration of treatment with statin.…”
Section: Discussionmentioning
confidence: 82%
“…An impairment of selenoprotein biosynthesis may be a factor in congestive heart failure, reminiscent of the dilated cardiomyopathies seen with selenium deficiency [23]. In HIV-infected adults with rosuvastatin treatment, over 48 weeks, Se concentrations increased significantly in the rosuvastatin group [24]. The reason for the inconsistency between our study and this study may be due to the different duration of treatment with statin.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is difficult to directly compare studies using different selenium status readouts [ 143 ]. Anti-retroviral therapies may also confound the selenium status [ 144 , 145 ]. However, some studies have not supported this notion [ 146 ].…”
Section: Immune Responses To Pathogensmentioning
confidence: 99%
“…In a cross-sectional study involving children with perinatally acquired HIV on stable ART for ≥6 mo, higher plasma selenium concentrations were associated with lower systemic inflammation and more elevated gut integrity markers (123). The plasma selenium concentration was associated with a higher proportion of T-cell activation (124) whereas zinc supplementation, in a pilot study, increased circulating zinc concentrations and modulated biomarkers associated with clinical comorbidities in HIV-positive adults (125). In a randomized, double-blind, placebo-controlled trial in infants (aged 6 wk, baseline) born to HIV-positive mothers in Tanzania, Liu et al (126) found that daily multivitamin supplementation (vitamin B complex, C and E) improved the children's hematologic status after 24 mo of intervention compared to a placebo group.…”
Section: Micronutrient Supplementationmentioning
confidence: 94%